Generational Technological Change: Effects of Innovation and Local Rivalry on Performance - Lawless, Michael W.; Anderson, Philip C. (Academy of Management Journal, 1996)
We tested the effects of innovation and market complexity on firm performance. Generational technological change?a major advance within a technology regime?fosters the emergence of niches and local rivalry. Findings from the U.S. microcomputer industry between 1982 and 1991 suggest accelerated markets reward innovativeness that differentiates firms within a niche but not across niches. Changing niches confers a short-term penalty. Strong performers adopt new technology quickly, without changing niches.